FEE AUDIT SEBAGAI PEMODERASI PENGARUH AUDITOR SWITCHING DAN AUDIT TENURE PADA KUALITAS AUDIT - Lee, David; Sukartha, I Made (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
This study aimed to get empirical evidence audit fee as the moderating influence of auditor switching and audit tenure on audit quality. This research was conducted on all companies listed in Indonesia Stock Exchange 2010-2015 period. The sampling method using purposive sampling. The number of samples of this research were 198 companies. Quality audits in this study using a proxy earnings surprise benchmark. Data analysis technique used is the logistic regression analysis. The results showed that the auditor switching does not affect the quality of the audit, audit tenure positive effect on the quality of the audit, the audit fee was not able to moderate the effect of switching auditors on audit quality and audit fees are not able to moderate the influence of audit tenure on audit quality.
Keywords: Fee Audit, Auditor Switching, Audit Tenure, Audit Quality